A Study of Political and Administrative Structures of Federalism and Good Governance in Indian Culture: Exploring the Dynamics of Federalism and Good Governance in India (Journal of Advances and Scholarly Researches in Allied Education, 2021)
This paper seeks to examine the essence of the federal structure of India, the changes that have taken place in the last 10 years and what is still to happen. First, we define briefly the main federal institutions in India, with a special emphasis on central-state transition mechanisms. These transfers are very comprehensive and are the most overt way to resolve inequalities among federal constituents. The role of political parties in communicating between central and state politics is an integral feature of federal institutions, inasmuch as the federalist nature is focused on representative democratic politics. In example of this, consider the extreme case of a notional democratic government with state-residue powers but a single, rigidly hierarchical political party dominates national governments as well as all states. Under this case, the results are the same as in a centralized, unitary structure. In India, different centralized political parties have represented, including the earlier congressional political bosses, the strictly-controlled, personalized approach of the later congress, the more institutionalized BJP hierarchy of political parties and the creation of specific regional parties. We then look at the facts on how the practical workings of the transition processes have influenced India's political economy. In the context of widening economic inequalities among States, we will discuss latest and potential reforms of the system of central-state transfer. It follows a study of broader existing and future changes in the federal institutions of India, including fiscal challenges and changes in the local government. Ultimately, we refer to other facets of economic change in India.